Back Cover: Molecular Rotors in Porous Organic Frameworks (Angew. Chem. Int. Ed. 4/2014). Issue 4 (20th January 2014) - Comotti, Angiolina; Bracco, Silvia; Ben, Teng; Qiu, Shilun; Sozzani, Piero
<x xml:space="preserve">Abstract</x> Para‐phenylene rings in porous aromatic frameworks rapidly flicker, resembling butterflies that flap their wings. In their Communication on page 1043 ff., P. Sozzani et al. demonstrate that these low‐density, yet robust covalent architectures can sustain extremely rapid rotational motion of the phenylene rings.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>